Characterization of Recycled Wood Chips, Syngas Yield, and Tar Formation in an Industrial Updraft Gasifier - Ehsan Oveisi (Environments, 2018)
In this study, the moisture content, calorific value, and particle size of recycled wood chips were measured. The wood chips were used to fuel an 8.5 MWth updraft gasifier to produce syngas for combustion in a steam-producing boiler. In-situ syngas composition and tar concentrations were measured and analyzed against biomass fuel properties. No efforts were made to adjust the properties of biomass or the routine operating conditions for the gasifier. A sampling device developed by CanmetENERGY-Ottawa (Ottawa, ON, Canada) was used to obtain syngas and tar samples. Wood chip samples fed to the gasifier were taken at the same time the gas was sampled. Results indicate that as the fuel moisture content increases from 20% to 35%, the production of CO drops along with a slight decrease in concentrations of H2 and CH4. Tar concentration increased slightly with increased moisture content and proportion of small fuel particles (3.15–6.3 mm). Based on the findings of this study, biomass fuel moisture content of 20% and particles larger than 6.3 mm (1/4″) are recommended for the industrial updraft gasifier in order to achieve a higher syngas quality and a lower tar concentration.